Upaya Meningkatkan Hasil Belajar Siswa Melalui Penerapan Problem Based Learning (PBL) Dalam Proses Pembelajaran Pendidikan Agama Katolik Pada Siswa Kelas III SD Negeri NO. 155710 Lobutua 1 - Indra Sarumpaet (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Student academic result is one of indicators that shows the success or failure of implementing the learning process at school. To obtain maximum student academic result, various efforts have been made, such as changing the curriculum which emerges new learning models in the learning process such as Problem Based Learning (PBL), Inquiry, Project Based Learning and so on.This research is aimed to determine the effect of implementing the Problem Based Learning learning model on improving student academic result. This research uses a quantitative approach with the One-Group Pretest-Posttest Design. The subjects of this research were 28 catholic’s students in 3rd grade of SD Negeri 155710 Lobutua 1. This research was held at SD Negeri 155710 Lobutua 1, Central Tapanuli, North Sumatra. This research was held in two cycles with different learning topics.The results of this research indicate that the application of the Problem Based Learning model in the learning process of Catholic Religious Education subjects both in cycle I and cycle II can improve the learning outcomes of 3rd grade students at SD Negeri No. 155710, Lobutua 1 with the significance value for each cycle are sig. 0.00 (F = 90.812) and sig. 0.00 (F = 89.787). The percentage increase in student academic result in each cycle are 40.75% and 36.84%.